Perspective Analysis Mashlahah Mursalah towards Tradition Mamangkeh And Maasok Gombak in the Pre-Wedding Procession in West Sumatra - Yandi, Akmal; Dahliana, Dina (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2024)
West Sumatra has various forms of different traditional traditions from various regions, from cities to remote areas, one of which is the Mamangkeh and Maasok Gombak traditions which are still a cultural phenomenon in society, these traditions have even become customary rules that will be given sanctions for people who violate them. The aim of this research is to analyze the view of Islamic Law from the perspective of Mashlahah Mursalah on the implementation of the mammangkeh and maasok Gombak traditions in West Sumatra. This study uses field research methods. The data source is primary data used consisting of interviews with traditional leaders, while secondary data comes from books and articles related to the research topic. This research results in the implementation of traditions mamangkeh and maasok Gombak after reviewing Mashlahah Mursalah, there are several maslahah contained in it, namely: firstly, the badoncek or fundraising event which can help with the bride and groom's wedding costs. Second, giving advice to prospective brides and grooms about getting married. Third, establishing a friendly relationship between a child and its bako parent.